Potret moralitas pribadi dalam novel karya anak - Suyatno, Suyatno (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This paper presents a description of personal morality from a children’s novel entitled Misteri Pedang Skinheald by Ataka (12 years old). Using thematic studies by the techniques of reading several times, it is found out that there are many information related to the children’s personal morality such as: responisbility, independence, honesty, purity, love, humility, self-consistency, justice, freedom and confidence. These morality portrait are developed into a narrative story without showing explicitly the moreal element within the plot from beginning to the end. Yet, the novel is packaged using simple, real and chronological order storyline.